MENGENAL ARTI PENTINGNYA KECEMASAN - Najwa Salsa Bila Wijaya; Anna Dina Kalifia (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Anxiety is a problem experienced by many people, both teenagers, adults and children. Anxiety has various causes, symptoms, and types. This research aims to recognize symptoms of anxiety in society and provide an understanding of how to identify these symptoms so that people can recognize when to seek professional help. This research is important to reduce the stigma of mental health problems and encourage people to be proactive in taking care of themselves. Educational steps such as outreach and training can help increase public understanding of anxiety symptoms. It is hoped that this research can make a positive contribution to changing people's attitudes and behavior regarding mental health.